2021
DOI: 10.1111/apa.15885
|View full text |Cite
|
Sign up to set email alerts
|

Considerable mortality and morbidity in neonates born below 500 gram

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In the future, it will be important to delineate underlying pathophysiological mechanisms (eg inflammation) that contribute to this pattern. Moreover, we agree with Goeral et al and Upadjyay et al 1,3 that the delivery of neonates at the threshold of viability comes with a plethora of difficult and complex ethical issues. In the grey zone of viability, evidence-based data are necessary to guide prenatal counselling and allow for informed shared decision-making.…”
Section: R E a D E R S ' F O R U Msupporting
confidence: 91%
See 3 more Smart Citations
“…In the future, it will be important to delineate underlying pathophysiological mechanisms (eg inflammation) that contribute to this pattern. Moreover, we agree with Goeral et al and Upadjyay et al 1,3 that the delivery of neonates at the threshold of viability comes with a plethora of difficult and complex ethical issues. In the grey zone of viability, evidence-based data are necessary to guide prenatal counselling and allow for informed shared decision-making.…”
Section: R E a D E R S ' F O R U Msupporting
confidence: 91%
“…103 (56.3%) were non-SGA (mean gestational age 25 + 1 weeks ±9.9 days and mean birth weight 662.6 ± 75.2 g) and 80 (43.7%) SGA (mean gestational age 26 + 6 weeks ±14.0 days and mean birth weight 543.9 ± 114.7 g). Of these SGA infants, 34/80 had a birth weight <3rd percentile, which is substantially lower than the rate reported by Goeral et al 1 Mortality was 24.1% (non-SGA: 30/103 (29.1%) and SGA: 14/80 (17.5%); p = 0.08). In our study, univariable logistic regression analysis revealed a significant protective effect of SGA status on pneumothoraces (OR 0.28, 95%-CI [0.11-0.69]), IVH (≥3) (OR 0.38; 95%-CI [0.15-0.67]) and seizures (OR 0.09, 95%-CI [0.01-0.76]), but NEC (≥2a) occurred more frequently in SGA neonates (p = 0.024).…”
Section: R E a D E R S ' F O R U Mmentioning
confidence: 58%
See 2 more Smart Citations
“…To date, only a small number of reports on the outcomes beyond the neonatal period of infants with a BW <500 g have been published. Recent studies revealed unfavorable outcomes: >50% of such infants reportedly have neurodevelopmental impairments (NDIs) at ages two and 3 years [6, 7]. The neurodevelopmental outcome beyond the neonatal period of Korean infants with a BW <500 g has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%